Spinal tuberculosis in a case of tubercular meningitis with hydrocephalus - Gautam, Shriram; Gautam, Vinod Kumar Singh (International Journal of Medicine, 2016)
Delayed diagnosis of tuberculosis of the brain and spine is associated with morbidity and mortality. Authors present a case to highlight the significance of thorough clinical work up, neuro-radiology and appropriate and prompt anti-tuberculous therapy in patients of CNS TB. Timely neurosurgical interventions in this patient who had developed spinal tuberculosis during the course of treatment for tuberculous meningitis (TBM) helped in reducing the morbidity and led to complete neurological recovery.